1957
DOI: 10.1084/jem.105.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Studies on Human Plasma Lipoproteins

Abstract: Some years ago, a series of h u m a n serum lipoproteins, distinguishable b y their h y d r a t e d densities and lipid-protein ratios were recognized and isolated b y ultracentrifugal techniques (1). Certain of these lipoproteins are invariably present in h u m a n serum and the concentrations of these and of others can be q u a n t i t a t i v e l y correlated with disease (2). N o difference in the lipoprotein distribution can be d e m o n s t r a t e d between serum and plasma. T h e purpose of this invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1964
1964
1978
1978

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In the T propositi and the There are other data attesting to some heterogeneity of HDL, however. Several subfractions isolated in the ultracentrifuge or by column chromatography have shown differences in metabolic behavior (15,21) and antigenic heterogeneity (22). The HDL protein may also show evidence of dissociation into two components under certain conditions (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the T propositi and the There are other data attesting to some heterogeneity of HDL, however. Several subfractions isolated in the ultracentrifuge or by column chromatography have shown differences in metabolic behavior (15,21) and antigenic heterogeneity (22). The HDL protein may also show evidence of dissociation into two components under certain conditions (23).…”
Section: Discussionmentioning
confidence: 99%
“…Immunochemical studies of the major density classes established clearly the antigenic heterogeneity of the human plasma lipoprotein system [1][2][3]. Recent chemical investigations have confirmed these earlier findings and demonstrated the presence of six antigenicalty distinct polypeptides designated as A-I,.…”
Section: Introductionmentioning
confidence: 86%
“…Finally, although only one major immunochemical study of high density lipoproteins (12) has concluded that they may be antigenically heterogeneous, there are other instances in which more than one form of this lipoprotein would appear to be present (13)(14)(15)(16). Thus, there is both direct and indirect evidence of inhomogeneity among high density lipoproteins.…”
mentioning
confidence: 99%